Evaluasi Kesiapan Modernisasi Sistem Irigasi di Daerah Irigasi Krueng Jreu Kabupaten Aceh Besar - Monisa Eka Yolanda; Syahrul Syahrul; Ichwana Ichwana (Fakultas Teknik, 2021)
Irrigation modernization as a fundamental transformation of irrigation water resources management which aims to increase the utilization of human resources and services provided to a farmer in an effective, efficient, and sustainable manner based on the five pillars of irrigation modernization. This study aims to evaluate the readiness of modernization Krueng Jreu Irrigation Area based on the 5 pillars of irrigation modernization. The research method was observation, interview, and research documentation. The results showed that the index value of modernization readiness in Krueng Jreu on the pillars of water availability with a value of 10, the pillars of irrigation infrastructure with a value of 19.8. Pillars of the irrigation management system with a value of 14, the pillars of irrigation management institutions with a value of 9 and the pillars of human resources for irrigation management with a value of 6. The total value of the index for modernization readiness in Krueng Jreu is 58.8 which is categorized as sufficient, irrigation modernization is postponed and must make improvements within 1-2 years.